2019
DOI: 10.1039/c9re00068b
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidation of 2-oxindole and barbituric acid derivatives under batch and continuous flow using an eco-friendly ethyl acetate solvent

Abstract: We have demonstrated the magnetically retrievable Fe(OH)3Fe3O4catalyzed C–H peroxidation of 2-oxindole and barbituric acid derivatives under batch and continuous flow process for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Organic peroxides offer a largely uncharted chemical space for the development of new medicinal agents with antimalarial, anthelmintic, anticancer, fungicidal, , antitubercular, and antiviral activities. Artemisinin, a natural peroxide recognized by the 2015 Nobel Prize in Medicine to Youyou Tu, and its synthetic analogues such as arterolane are important antimalarial drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Organic peroxides offer a largely uncharted chemical space for the development of new medicinal agents with antimalarial, anthelmintic, anticancer, fungicidal, , antitubercular, and antiviral activities. Artemisinin, a natural peroxide recognized by the 2015 Nobel Prize in Medicine to Youyou Tu, and its synthetic analogues such as arterolane are important antimalarial drugs.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the nucleophilic attack can proceed via the S N 1 pathway. On the contrary, in the case of the azidation of peroxyoxindoles, at first Amberlyst-15 leads to the deprotection of 4 to give A . In the next step, the distant oxygen atom of A coordinates to TMS because of the high affinity of oxygen for silicon, thereby making N 3 – free nucleophile.…”
Section: Resultsmentioning
confidence: 99%
“…The graphical solution of Equation (10) in semilog coordinates (ln ½1 − m t /m ∞t) (Figure 7) allows us to calculate D 2 :…”
Section: Oz Release From Mps and Fsmentioning
confidence: 99%
“…The discovery of the natural peroxide artemisinin [1][2][3], which has antimalarial properties, was the beginning of the development of biologically active peroxides (Figure 1). It has been found that cyclic peroxides have antimalarial [4][5][6][7][8][9][10][11][12], antiparasitic [13][14][15][16][17][18][19], anticancer [20][21][22][23][24][25][26][27][28][29][30][31], antiviral [32][33][34], and fungicidal [18,35,36] activities. On the basis of the fully synthetic peroxide arterolane, which contains a 1,2,4-trioxolane (ozonide) fragment, has been created an antimalarial drug of the latest generation-Synriam [37].…”
Section: Introductionmentioning
confidence: 99%